Two-phase flow in open-cell metal foams with application to aero-engine separators - Piazera de Carvalho, Thiago (2016)
Oil-air separation is a key function in aero engines with closed-loop oil systems. Aero-engine separators are employed to separate oil from air before being released overboard. Typically, these devices make use of a porous medium such as an open-cell metal foam, in order to enhance oil separation. Although quite scarce, there has been some research aimed at developing a suitable modelling framework for aero-engine separators. However, numerical modelling of the air/oil flow through the open-cell metal foams employed in aero-engine separators has never been properly addressed.